Developing English Writing Assessments of Procedure Text for Local Culinary Program - Siregar, Tiarnita Maria Sarjani Br.; Natsir, Muhammad; Fibriasari, Hesti; Rahmadany, Savitri (JOLLT Journal of Languages and Language Teaching, 2025)
This study investigates the enhancement of English writing assessments focusing on local cuisine as a thematic subject. A comprehension test was employed as a key instrument to measure students’ progress and evaluate their understanding of the lessons delivered. Following the test administration, the teacher utilized appropriate assessment methods to ensure accurate evaluation. The primary objective of this research is to develop and refine writing assessments for English language learners, particularly within the context of local culinary topics. The study adopted a Research and Development (R&D) approach, structured into six distinct stages: (1) information and data collection, (2) data analysis, (3) development of new writing assessments, (4) expert validation, (5) revision of assessments, and (6) finalization of the validated tool. Data was gathered through interviews and questionnaires distributed to English teachers. Two evaluatorsâ€”an English lecturer and an English instructorâ€”provided critical validation of the assessment tools. The evaluation framework emphasized three core competencies: attitude, knowledge, and skill, incorporating a formative and authentic assessment approach. The writing tasks centered on topics such as local dishes, pastries, and beverages, integrating cultural elements into language learning. The assessment instruments underwent validation by two professionals, yielding an excellent classification score of 93%, indicating the reliability and effectiveness of the developed tools. The study underscores the significance of culturally relevant content in English language learning, fostering deeper engagement and contextual understanding among students. By integrating local cuisine into writing assessments, the research highlights the potential to enhance both linguistic competence and cultural awareness, promoting a more holistic educational experience.